Использование иппотерапии в физической реабилитации больных с различной патологией = Use hippotherapy in physical rehabilitation of patients with different pathologies - Kokhan, S. T.; Pateyuk, A. V.; Mingalova, M. S.; Grygus, I. M. (Journal of Education, Health and Sport, 2015)
Kokhan S. T., Pateyuk A. V., Mingalova M. S., Grygus I. M. Использование иппотерапии в физической реабилитации больных с различной патологией = Use hippotherapy in physical rehabilitation of patients with different pathologies. Journal of Education, Health and Sport. 2015;5(2):289-296. ISSN 2391-8306. DOI: 10.5281/zenodo.17836 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A289-296 https://pbn.nauka.gov.pl/works/561265 http://dx.doi.org/10.5281/zenodo.17836 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.02.2015. Использование иппотерапии в физической реабилитации больных с различной патологией Use hippotherapy in physical rehabilitation of patients with different pathologies С. Т. Кохан, А. В. Патеюк, М. С. Мингалова, И. М. Григус1 S. T. Kokhan, A. V. Pateyuk, M. S. Mingalova, I. M. Grygus1 Забайкальский государственный университет (г. Чита, Россия), Национальный университет водного хозяйства и природопользования1 (г. Ровно, Украина) Transbaikal State University (Chita, Russia), National University of Water Management and Nature Resources Use (Rovno, Ukraine) 1 Аннотация. Главной особенностью медико-социальной реабилитации инвалидов в Забайкальском крае является особенность климата – короткий теплый период и длительный период с отрицательной температурой до -40 С и ниже зимой, что не позволяет использовать некоторые объекты зимой. Хотя имеются учреждения круглогодичного использования. Представленные данные позволяют заключить о том, что спорт, в данном случае – конный, является одной из важных форм технологии реабилитации инвалидов. Наши результаты продемонстрировали значительные положительные изменения в показателях реабилитации у инвалидов при использовании иппотерапии. Это доказывает значимость данной технологии для всего мира в целом, ведь спортсмен, не важно инвалид или здоровый человек. Ключевые слова: инвалид, реабилитация, иппотерапия. Abstract. The main feature of medical and social rehabilitation of persons with disabilities in the Trans-Baikal Territory is a feature of the climate – a short warm season and a long period with negative temperatures up to-40 C and lower in the winter, which does not use some of the objects in the winter. Although there are establishments all year round use. These data allow us to conclude that sport, in this case – horse is one of the important forms of technology Rehabilitation. Our results showed significant positive changes in terms of rehabilitation of persons with disabilities when using hippotherapy. This proves the importance of this technology for the world as a whole, as an athlete, whether disabled or healthy person. Keywords: disabled, rehabilitation, hippotherapy.